The Local Explanatory Model: A Study of Assumed Causes of Tuberculosis in Rural Nepal - Engelbrektsson, Ulla-Britt; Subedi, Madhusudan (Dhaulagiri Journal of Sociology and Anthropology, 2016)
Tuberculosis (TB) constitutes one of the major public health problems in Nepal. Our theoretical framework, in this paper, is to explore people's understanding of the culturally constructed reality, the local explanatory model, for causes of Tuberculosis. The ethnographic data were collected from 'Solubang' village of Pyuthan district in 2005 and 2012/13. The finding shows that assumed and suggested cause(s) of TB are multiple but most often within a framework of great uncertainty. Compared to 2005, people were better aware of the need for timely treatment in 2012/13. The arrival of the biomedical anti-TB medicines has changed the situation for the better and is widely recognized but perception on causes of TB and its prevalence have not changed drastically, and mortality rates have not decreased at the speed hoped for.